How COVID-19 Will Change Health, Hospitality and Senior Facility Design - Shepley, McCuskey Mardelle; Kolakowski, Heather; Ziebarth, Nicolas; Valenzuela-Mendoza, Ellie (Frontiers in Built Environment, 2021)
Based on recent experiences with the COVID-19 pandemic, designers and design researchers are crafting guidelines for the development of future environments. In this context, this paper focuses on future best practices regarding environments for health, hospitality and senior care. Methods. An extensive literature review was conducted, the results of which were distributed to a group of experts (N=12) specializing in health, hospitality and design. After receiving their input, expert focus groups were conducted to further explore the proposed concepts. The document was revised based on the contributions of these field experts, resubmitted for additional input, and ultimately summarized in this paper. Results. Based on the literature review and expert input, dozens of recommendations were made regarding post-COVID health, hospitality and seniors environments. Healthcare facilities will require additional space, access to the outdoors, service hubs, and flexibility in garage and use of outdoor space. Hospitality settings will employ new cleaning methods, use of robotics, improved HVAC, Wellness programming, workspace options, and flexible food service operations. Senior facilities will engage more technology, socially distance visiting facilities, increase access to nature, and smaller scale residential clusters. Discussion. By considering health and hospitality simultaneously, we come to understand the symbiotic benefits of applying goals from one sector to the other. Senior living environments are an excellent example of this approach in action. By implementing some of the proposed design recommendations generated by this research, we will be better prepared to face future challenges.